2016
DOI: 10.1002/ptr.5734
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacology ofCitrus bergamia: A Systematic Review

Abstract: Citrus bergamia Risso et Poiteau ("Bergamot") originated from the Mediterranean ecoregion (southern Italy, Calabria). Bergamot essential oil (BEO) is used in perfumes, cosmetics, and for stress reduction. Juice from C. bergamia has been used for hyperlipidemia. We evaluated literature published on C. bergamia clinical applications. Clinical trials on C. bergamia not combined with other substances, published in English, were searched. We selected ten articles, six describing BEO effects on stress, three reporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 43 publications
1
61
0
1
Order By: Relevance
“…Furthermore, we revealed that GL impairs IMQ‐induced type I IFN production by pDCs. A search of the literature for citrus products used in psoriasis research found only bergamot essential oil (BEO) from Citrus bergamia to have been studied in this way . This report is therefore the first demonstration of the ameliorating effect of GL (citrus peel extracts) on psoriasis.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, we revealed that GL impairs IMQ‐induced type I IFN production by pDCs. A search of the literature for citrus products used in psoriasis research found only bergamot essential oil (BEO) from Citrus bergamia to have been studied in this way . This report is therefore the first demonstration of the ameliorating effect of GL (citrus peel extracts) on psoriasis.…”
Section: Discussionmentioning
confidence: 88%
“…Inter-individual variations have also been observed, probably due to the different composition of the colonic microflora which can affect their metabolism in different ways. Nevertheless, despite bioavailability problems, numerous experimental and clinical data have demonstrated the ability of Citrus flavonoids to exert important systemic pharmacological effects [14,281,282]. In addition, Citrus flavonoids also display neuroprotective effects [283,284], suggesting that they are able to cross the blood–brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The fruit has a yellow peel and is the size of an orange. BEO also presents a variable percentage (4-7%) of nonvolatile compounds, such as pigments, waxes, coumarins, and psoralens (Mannucci et al, 2017). Fresh juice from bergamot has been studied to evaluate the polyphenolic composition by HPLC-DAD analysis and total polyphenols content by UV method (Picerno et al, 2011).…”
Section: Introductionmentioning
confidence: 99%